Seasonal variations of microbial community in a full scale oil field produced water treatment plant - Q. Xie; S. Bai; Y. Li; L. Liu; S. Wang; J. Xi (Global Journal of Environmental Science and Management)
This study investigated the microbial community in a full scale anaerobic baffled reactor and sequencing batch reactor system for oil-produced water treatment in summer and winter. The community structures of fungi and bacteria were analyzed through polymerase chain reaction–denaturing gradient gel electrophoresis and Illumina high-throughput sequencing, respectively. Chemical oxygen demand effluent concentration achieved lower than 50 mg/L level after the system in both summer and winter, however, chemical oxygen demand removal rates after anaerobic baffled reactor treatment system were significant higher in summer than that in winter, which conformed to the microbial community diversity. Saccharomycotina, Fusarium, and Aspergillus were detected in both anaerobic baffled reactor and sequencing batch reactor during summer and winter. The fungal communities in anaerobic baffled reactor and sequencing batch reactor were shaped by seasons and treatment units, while there was no correlation between abundance of fungi and chemical oxygen demand removal rates. Compared to summer, the total amount of the dominant hydrocarbon degrading bacteria decreased by 10.2% in anaerobic baffled reactor, resulting in only around 23% of chemical oxygen demand was removed in winter. Although microbial community significantly varied in the three parallel sulfide reducing bacteria, the performance of these bioreactors had no significant difference between summer and winter.